2013
DOI: 10.1029/2012gb004413
|View full text |Cite
|
Sign up to set email alerts
|

Decadal changes in dissolved inorganic carbon in the Pacific Ocean

Abstract: [1] Using high-quality data sets obtained about a decade apart, we examined the changes of dissolved inorganic carbon in the Pacific Ocean, separating anthropogenic and natural CO 2 . Observations along three transoceanic sections along 47°N, 179°E, and 17°S showed both decadal increases (>20µmol kg , except in the western subarctic Pacific. In contrast, in subtropical regions of both hemispheres, we found an increasing trend of >10 µmol kg -1 in oceanic uptake of anthropogenic CO 2 , reflecting accumulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 48 publications
7
31
1
Order By: Relevance
“…Kouketsu et al () estimated Pacific C anth increased by 8.4 (±0.5) PgC between 50°S and 65°N in the earlier decade (1995 to 2005), where we find 7.7 (±1.1) PgC accumulation (Table ). The majority of this (statistically insignificant) discrepancy originates in the 20°S to 50°S latitude band where Murata et al () found more C anth than we do along P06 (Table ).…”
Section: Resultssupporting
confidence: 72%
“…Kouketsu et al () estimated Pacific C anth increased by 8.4 (±0.5) PgC between 50°S and 65°N in the earlier decade (1995 to 2005), where we find 7.7 (±1.1) PgC accumulation (Table ). The majority of this (statistically insignificant) discrepancy originates in the 20°S to 50°S latitude band where Murata et al () found more C anth than we do along P06 (Table ).…”
Section: Resultssupporting
confidence: 72%
“…The principal contributor to ΔΩ was increases of anthropogenic CO 2 (section 6). The faster rates of decrease in our results can therefore be attributed to rapid accumulation of anthropogenic CO 2 in the South Pacific [ Murata et al , ; Waters et al , ; Feely et al , ; Kouketsu et al , ]. In the case of region 3, we believe that another factor also contributed to hastening the progression of OA.…”
Section: Discussionsupporting
confidence: 63%
“…In the western part of section P21, the Ω arg saturation horizon was at a depth of about 1200 dbar in Antarctic Intermediate Water (Figure ). This finding suggests that its upward migration was probably accelerated by anthropogenic CO 2 from the Southern Ocean [ Kouketsu et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on CT changes between the two repeated visits of the longitudinal P21 line (18° S close to the OUTPACE transect) in 1994 and 2009, Kouketsu et al (2013) shows faster increase of CANT in the western part than in the eastern part of the section. ) for the upper water column at the latitude of OUTPACE area in good agreement with our estimates in WGY in the upper water column.…”
Section: Hydrological Context Along the Outpace Transectmentioning
confidence: 99%
“…Even if, due to its remoteness from land, it remains largely under-explored by oceanographic vessels compared to other oceanic areas, the Pacific Ocean has been covered by cruises along long sections (the "P sections" from the WOCE program). Most of these sections have been revisited during the last years (see for example Sabine et al, 2008or Kouketsu et al, 2013. In a recent study based on repeated sections in the Pacific (P16 at 150W),…”
Section: Introductionmentioning
confidence: 99%